Vault an Inspector Wexford novel - Rendell, Ruth (New York : Scribner, 2011)
When four bodies are discovered in the same underground sewer 12 years after the events of A Sight for Sore Eyes, former Chief Inspector Wexford is pulled out of retirement to follow a complex trail to the original murders only to have his life thrown into turmoil by a devastating personal tragedy
Sequel to: A sight for sore eyes.
Keywords: Wexford, Inspector (Fictitious character); Police -- England -- Sussex; Murder; London (England); Sussex (England); Mystery fiction